Lithium-sulfur battery positive electrode material and preparation method thereof and lithium-sulfur battery positive electrode sheet
By using bimetallic selenide structure wrapped in two-dimensional MXene nanosheets in lithium sulfur batteries, the problem of poor circulation of lithium sulfur batteries is solved, and electrode materials with high specific capacity and long cycle life are achieved. Specifically, ZIF-8@ The combination method of ZIF-67 dodecahedron, HZnSe-CoSe porous hollow dodecahedron and MXene colloids forms a 45@HZnSe-CoSe/M/S composite material and is mixed with carbon black and binder to coat, which significantly improves the Battery conductivity and cycle stability.
Patent Information
- Application Number
- CN202211550697.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-12-05
AI Technical Summary
During the charging and discharging process, lithium-sulfur batteries have poor cycle properties due to shuttle effect and poor conductivity of elemental sulfur electrons/ion.
Bimetal selenide (45@HZnSe-CoSe/M) dodecahedral structure wrapped in two-dimensional MXene nanosheets is used as the cathode material of lithium sulfur batteries. ZIF-8@ZIF-67 dodecahedral and HZnSe-CoSe porous hollow The combination method of dodecahedron and MXene colloid forms a 45@HZnSe-CoSe/M/S composite material, and is coated with carbon black and binder to improve the conductivity and cycle life of the battery.
The discharge capacity is 1299.8mAh·g-1 at 0.1C current density, and the initial Coulomb efficiency is 99.3%. The discharge capacity of 552.7mAh·g-1 can still be maintained after 500 cycles. The capacity attenuation rate per cycle is only 0.07%. , significantly improves the specific capacity and cycle life of the electrode material.
Smart Images

Figure CN115832251B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-sulfur batteries, and in particular to a lithium-sulfur battery positive electrode material and a preparation method thereof, and a lithium-sulfur battery positive electrode sheet. Background Art
[0002] At present, the demand for high-performance secondary batteries is growing, while the energy density of traditional lithium-ion batteries has reached its limit. It is difficult to achieve a major breakthrough in the short term and it is difficult to meet people's needs. Therefore, it is necessary to develop new secondary batteries with higher energy and power density and longer cycle life. Among many new secondary battery systems, lithium-sulfur batteries have a very high theoretical specific capacity (1675mAh·g -1 ) and theoretical energy density (2600Wh·kg -1 ) and the advantages of abundant reserves, low price and environmental friendliness of the active substance sulfur, it is considered to be one of the most promising high-efficiency energy storage devices of the next generation.
[0003] However, in the development of lithium-sulfur batteries, some prominent problems have restricted its development, including poor conductivity of sulfur, volume expansion during discharge, and the generated polysulfides causing the shuttle effect, etc. Therefore, finding and developing suitable sulfur cathode materials to alleviate the above problems is the key to overcoming difficulties, and it is also a hot spot and difficulty in research. Summary of the invention
[0004] The main purpose of the present invention is to provide a lithium-sulfur battery positive electrode material and a preparation method thereof and a lithium-sulfur battery positive electrode sheet, so as to solve the problem of poor cyclability of lithium-sulfur batteries in the prior art during the charge and discharge process caused by the "shuttle effect" and poor conductivity of elemental sulfur electrons / ions.
[0005] According to one aspect of the present application, a lithium-sulfur battery cathode material is proposed, wherein the lithium-sulfur battery cathode material comprises a two-dimensional MXene nanosheet encapsulating a bimetallic selenide (45@HZnSe-CoSe / M) dodecahedral structure.
[0006] The HZnSe-CoSe dodecahedron is a porous hollow rhombic dodecahedron, and the average diameter of the porous hollow rhombic dodecahedron particles is 580 nm.
[0007] According to another aspect of the present application, a method for preparing a positive electrode material for a lithium-sulfur battery is also proposed, which includes: preparing ZIF-8@ZIF-67 dodecahedron, preparing 45@HZIF based on the ZIF-8@ZIF-67 dodecahedron, and preparing HZnSe-CoSe porous hollow dodecahedron based on 45@HZIF; preparing MXene colloid; mixing 45@HZnSe-CoSe porous hollow dodecahedron with MXene colloid to obtain two-dimensional MXene nanosheets wrapped in 45@HZnSe-CoSe dodecahedron (45@HZnSe-CoSe / M); and performing infiltration treatment on 45@HZnSe-CoSe / M to obtain a 45@HZnSe-CoSe / M / S composite material.
[0008] The steps of preparing ZIF-8@ZIF-67 dodecahedron include: dissolving cobalt nitrate hexahydrate (Zn(NO3)2·6H2O) and 2-methylimidazole (MeIm) in methanol respectively, mixing the two solutions, and obtaining ZIF-8 through a white precipitate in the mixed solution; ultrasonically dispersing ZIF-8 in methanol to obtain a ZIF-8 dispersion; dissolving Co(NO3)2·6H2O and MeIm in methanol respectively, and adding the two solutions to the ZIF-8 dispersion respectively, and obtaining ZIF-8@ZIF-67 dodecahedron through a precipitate in the mixed solution.
[0009] Among them, the steps of preparing 45@HZIF according to ZIF-8@ZIF-67 dodecahedron and preparing HZnSe-CoSe porous hollow dodecahedron according to 45@HZIF include: obtaining ZIF-8@ZIF-67 dispersion according to ZIF-8@ZIF-67; adding tannic acid aqueous solution to the ZIF-8@ZIF-67 dispersion to obtain 45@HZIF dodecahedron; and performing selenization reaction on 45@HZIF to obtain 45@HZnSe-CoSe porous hollow dodecahedron.
[0010] The steps of preparing MXene colloid include: mixing Ti3AlC2-MAX phase ceramic, LiF and HCl to obtain a mixed solution; stirring the mixed solution to allow HF generated in the mixed solution to etch Al in MAX; washing the mixed solution with deionized water and centrifuging it; adding deionized water to the precipitate of the mixed solution for ultrasonic treatment, and collecting the MXene colloid in the upper layer of the solution after ultrasonic treatment.
[0011] According to another aspect of the present application, a lithium-sulfur battery positive electrode sheet is also proposed, which includes: a current collector and a coating layer coated on the surface of the current collector, wherein the coating layer includes a 45@HZnSe-CoSe / M / S composite material prepared according to the preparation method according to any one of claims 3 to 6.
[0012] Wherein, the coating layer also includes carbon black and a binder.
[0013] Wherein, the mass ratio of the 45@HZnSe-CoSe / M / S composite material, the carbon black and the binder is 7:2:1.
[0014] Wherein, the mass ratio of the 45@HZnSe-CoSe / M / S composite material, the carbon black and the binder is 6:3:1.
[0015] The S@Co3S4 / CN nano-box cathode material according to the technical solution of the present invention has a discharge capacity of 1299.8 mAh·g at a current density of 0.1C by testing the cathode material. -1 The initial Coulombic efficiency is 99.3%; at a current density of 1C, it can still maintain 552.7mAh·g after 500 cycles. -1 The discharge capacity is very good, and the capacity decay rate per cycle is only 0.07%. The electrode material has high specific capacity and long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 is a flow chart according to an embodiment of the present invention;
[0018] Figure 2 Schematic diagram of the formation of 45@HZnSe-CoSe / M / S positive electrode material according to an embodiment of the present invention;
[0019] Figure 3 is a flow chart according to another embodiment of the present invention;
[0020] Figure 4A is a transmission electron microscope image of a 15@HZIF dodecahedron according to an embodiment of the present invention;
[0021] Figure 4B is a transmission electron microscope image of a 30@HZIF dodecahedron according to an embodiment of the present invention;
[0022] Figure 4C is a transmission electron microscope image of a 45@HZIF dodecahedron according to an embodiment of the present invention;
[0023] Figure 4D is a transmission electron microscope image of a 60@HZIF dodecahedron according to an embodiment of the present invention;
[0024] Figure 4Eis a transmission electron microscope image of a 45@HZnSe-CoSe dodecahedron according to an embodiment of the present invention;
[0025] Figure 4F is a transmission electron microscope image of a 45@HZnSe-CoSe / M dodecahedron according to an embodiment of the present invention;
[0026] Figure 5 It is a schematic diagram of XRD analysis of 15@HZnSe-CoSe, 30@HZnSe-CoSe, 45@HZnSe-CoSe, and 60@HZnSe-CoSe according to an embodiment of the present invention;
[0027] Figure 6 It is a schematic diagram of electrochemical impedance spectra of 15@HZnSe-CoSe / S, 30@HZnSe-CoSe / S, 45@HZnSe-CoSe / S, and 60@HZnSe-CoSe / S according to an embodiment of the present invention;
[0028] Figure 7 It is a schematic diagram of the specific capacity and Coulomb efficiency curves of 15@HZnSe-CoSe / S, 30@HZnSe-CoSe / S, 45@HZnSe-CoSe / S, and 60@HZnSe-CoSe / S positive electrode materials cycled 100 times at 0.2C according to an embodiment of the present invention;
[0029] Figure 8 Schematic diagram of rate performance of 45@HZnSe-CoSe / S and 45@HZnSe-CoSe / M / S cathode materials at 0.1C-2C current density according to an embodiment of the present invention;
[0030] Fig. 9 Schematic diagram of the specific capacity and Coulomb efficiency curves of the 45@HZnSe-CoSe / S and 45@HZnSe-CoSe / M / S positive electrode materials according to an embodiment of the present invention after 100 cycles at 0.2C. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention and the corresponding drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] The technical solutions provided by various embodiments of the present invention are described in detail below in conjunction with the accompanying drawings.
[0033] According to an embodiment of the present invention, a lithium-sulfur battery positive electrode material is provided, wherein the lithium-sulfur battery positive electrode material comprises a bimetallic selenide (45@HZnSe-CoSe / M) dodecahedral structure wrapped by two-dimensional MXene nanosheets.
[0034] The present invention adopts acid etching technology to etch the ZIF precursor to form four hollow structures of different degrees, wherein the electrode material obtained has the best electrochemical performance when etching for 45 minutes, indicating that too much or too little bimetallic compound will affect the performance of the battery. On the basis of this structure, a conductive two-dimensional material MXene is added to obtain a 45@HZnSe-CoSe / M composite material. The obtained 45@HZnSe-CoSe has a rich pore structure, and ZnSe and CoSe can effectively adsorb lithium polysulfide during charging and discharging, thereby preventing it from dissolving in the electrolyte and alleviating the shuttle effect, thereby improving the electrochemical performance and cycle life of the material; the hollow structure has a high specific surface area and a large space, which can alleviate the volume expansion / contraction of the battery during charging and discharging; the two-dimensional MXene coating layer gives the positive electrode material good electron transmission performance on the one hand, and on the other hand, it can also prevent the combination of sulfur and lithium, further improving the electrochemical performance of the material.
[0035] According to an embodiment of the present invention, a method for preparing a positive electrode material for a lithium-sulfur battery is also provided. Figure 1 and Figure 2 , the method comprising:
[0036] Step S102, preparing ZIF-8@ZIF-67 dodecahedron, preparing 45@HZIF based on ZIF-8@ZIF-67 dodecahedron, and preparing HZnSe-CoSe porous hollow dodecahedron based on 45@HZIF.
[0037] (1) First, it is necessary to prepare ZIF-8@ZIF-67 dodecahedrons, which specifically includes: dissolving cobalt nitrate hexahydrate (Zn(NO3)2·6H2O) and 2-methylimidazole (MeIm) in 150 ml of methanol and stirring for 30 minutes. Then, the two solutions are quickly mixed and stirred at room temperature for 24 hours. Then, the obtained white precipitate is centrifuged and washed with methanol, and dried at 60°C for 12 hours to obtain ZIF-8. After that, ZIF-8 is ultrasonically dispersed in methanol to obtain a ZIF-8 dispersion as the "seed" for the growth of ZIF-67; then, Zn(NO3)2·6H2O and MeIm are dissolved in 100 ml of methanol solution, and then the two solutions are added to the ZIF-8 dispersion, and stirred at room temperature for 24 hours. Finally, the precipitate is centrifuged, washed and dried to obtain a bright purple sample, that is, the ZIF-8@ZIF-67 dodecahedron structure is obtained.
[0038] (2) 45@HZIF was prepared based on ZIF-8@ZIF-67 dodecahedron. Specifically, 1.0 g of ZIF-8@ZIF-67 was ultrasonically dispersed in 2 ml of ethanol solution and stirred for 20 minutes to obtain a ZIF-8@ZIF-67 dispersion. Then, 0.25 g of tannic acid was dissolved in 48 ml of deionized water and stirred for 30 minutes to obtain a tannic acid aqueous solution. While the ZIF-8@ZIF-67 dispersion was stirred at high speed, the tannic acid aqueous solution was slowly added to the ZIF-8@ZIF-67 dispersion and aged for 45 minutes. Then, the precipitate was centrifuged, washed with deionized water and methanol, and dried to obtain 45@HZIF. In the same steps for preparing the tannic acid aqueous solution and the ZIF-8@ZIF-67 dispersion, the aging time was changed to 15 minutes, 30 minutes, and 1 hour, respectively, to obtain 15@HZIF, 30@HZIF, and 60@HZIF.
[0039] (3) Prepare HZnSe-CoSe porous hollow dodecahedron based on 45@HZIF, specifically: take 0.5g of the above-prepared 45@HZIF material and 1.0g of selenium powder and put them into two dry pots respectively, place them in the downstream and upstream of the tube furnace, and calcine them at 800℃ for 3 hours under N2 protection to obtain the final material 45@HZnSe-CoSe porous hollow rhombic dodecahedron. The other three materials (15@HZIF, 30@HZIF, 60@HZIF) are also obtained by similar methods to obtain 15@HZnSe-CoSe, 30@HZnSe-CoSe, 60@HZnSe-CoSe composite materials, which will not be repeated here.
[0040] Step S104, a step of preparing MXene colloid, specifically comprises:
[0041] (1) First, 1.0 g of LiF was dispersed in a solution containing 5 mL of deionized water and 15 mL of HCl (12 mol / L), and then 1.0 g of Ti3AlC2(MAX) powder was slowly added to prevent overheating.
[0042] (2) Next, the mixed solution of step (1) was stirred at a constant temperature (35° C.) for 24 hours on a magnetic stirrer to allow the HF generated by the reaction to fully etch the Al in the MAX, that is, to etch away the "A" layer in the MAX phase.
[0043] (3) After 24 hours, the mixed solution of step (2) was collected, centrifuged, and washed with deionized water for 4-5 times until the pH value of the supernatant of the mixed solution reached about 6, and the precipitate was collected to obtain stacked multilayer MXene.
[0044] (4) Collect the precipitate after centrifugation, add 200 mL of deionized water, and then ultrasonicate for 4 h. After the ultrasonication, centrifuge at 3500 rpm for 1 h to collect the upper MXene colloid. By peeling, the single-layer MXene can be ensured to remain in the upper layer, while the unpeeled multilayers remain in the lower layer. The upper colloid is collected for use and the lower layer is discarded. Among them, MXene is a two-dimensional layered fragment with a negative charge and excellent hydrophilicity, so it is called a colloid.
[0045] Step S106, 45@HZnSe-CoSe porous hollow dodecahedron is mixed with MXene colloid to obtain 45@HZnSe-CoSe dodecahedron (45@HZnSe-CoSe / M) wrapped with two-dimensional MXene nanosheets. Among them, 45@HZnSe-CoSe dodecahedron carries a positive charge, and under electrostatic interaction, the two components of MXene colloid and 45@HZnSe-CoSe dodecahedron can be assembled together. Specifically, 45@HZnSe-CoSe is ultrasonically dispersed in methanol, and then MXene colloid is added under rapid stirring. Through electrostatic interaction, the two components are successfully assembled, and finally 45@HZnSe-CoSe / M is collected by centrifugal washing and drying. Coating the MXene sheet outside the bimetallic selenide 45@HZnSe-CoSe can improve the conductivity of the battery, and further alleviate the shuttle effect of polysulfides, thereby improving the electrochemical performance of the battery.
[0046] Step S108, 45@HZnSe-CoSe / M is subjected to sulfurization treatment to obtain a 45@HZnSe-CoSe / M / S composite material. Specifically, the prepared 45@HZnSe-CoSe / M dodecahedron and elemental sulfur are mixed and ground for 30 minutes, and then kept at 155°C for 12 hours to obtain a 45@HZnSe-CoSe / M / S material. The other three materials (15@HZnSe-CoSe, 30@HZnSe-CoSe, 60@HZnSe-CoSe) are also obtained by a similar method to obtain 15@HZnSe-CoSe / S, 30@HZnSe-CoSe / S, and 60@HZnSe-CoSe / S composite materials, which will not be repeated. The above materials can be used to prepare lithium-sulfur battery positive electrode materials. In the above steps, grinding can make the two components fully mixed, and 155 degrees Celsius is selected because elemental sulfur has the best fluidity at this temperature and is most likely to enter the voids of the HZnSe-CoSe dodecahedron.
[0047] According to an embodiment of the present application, a method for preparing a positive electrode sheet of a lithium-sulfur battery is also provided, referring to Figure 3 ,exist Figure 1 Based on the illustrated embodiment, the method further comprises:
[0048] Step S110, preparing slurry. The 45@HZnSe-CoSe / M / S composite material prepared in step S108 is mixed with carbon black and a binder to form a slurry, wherein the mass ratio of the 45@HZnSe-CoSe / M / S composite material, carbon black and binder can be 7:2:1 or 6:3:1.
[0049] Step S112, uniformly coating the slurry on the current collector of the positive electrode sheet of the lithium-sulfur battery, and drying at 60° C. for 12 hours under vacuum to prepare an electrode sheet.
[0050] The current collector may be metal foil, foam metal, foam carbon, carbon paper, carbon felt or carbon cloth.
[0051] Among them, the binder can be an oil-soluble binder, such as polyvinylidene fluoride; when the binder is an oil-soluble binder, the solvent for dissolving the binder is N-methyl-2-pyrrolidone; or the binder can be a water-soluble binder, such as: polytetrafluoroethylene, polyethylene oxide, LA133, polymethyl methacrylate, β-cyclodextrin, agar, starch, sodium carboxymethyl cellulose, polybutadiene rubber, styrene-butadiene rubber, etc.; when the binder is a water-soluble binder, the solvent is water.
[0052] According to an embodiment of the present application, a lithium-sulfur battery positive electrode sheet is also provided, which includes: a current collector and a coating layer coated on the surface of the current collector, wherein the coating layer includes a 45@HZnSe-CoSe / M / S composite material. The coating layer also includes carbon black and a binder, and the mass ratio of the 45@HZnSe-CoSe / M / S composite material, carbon black and the binder is 7:2:1 or 6:3:1.
[0053] refer to Figures 4A to 4F , Figures 4A to 4D The morphological characteristics of ZIF-8@ZIF-67 dodecahedron etched by tannic acid after 15, 30, 45 and 60 minutes, respectively. As the etching time increases, the morphology of the material evolves from a core-shell type to a completely hollow structure. Figure 4E The morphology of 45@HZnSe-CoSe is shown, indicating that the selenization reaction does not affect the structural integrity of the dodecahedron. Figure 4F The morphology of 45@HZnSe-CoSe / M shows that the dodecahedron is covered with many layers, indicating that MXene and 45@HZnSe-CoSe materials are successfully composited. Figures 5 to 9The present invention obtains hollow dodecahedrons of different degrees by acid etching technology, and then prepares HZnSe-CoSe dodecahedrons by selenization reaction, and then prepares HZnSe-CoSe / S composite positive electrode material by sulfurization method. It can be seen from the test of four positive electrode materials that 45@HZnSe-CoSe / S positive electrode material has the smallest charge transfer resistance, and the initial discharge specific capacity is 740mAh·g at a current density of 0.2C. -1 After 100 cycles, the discharge capacity is still 386 mAh g -1 , and the coulombic efficiency is always maintained above 98% (see Table 1 for comparison data). This shows that the hollow structure electrode obtained by etching for 45 minutes has the most stable cycle life. Therefore, on the basis of etching for 45 minutes, the conductive two-dimensional material MXene is added to obtain the 45@HZnSe-CoSe / M / S positive electrode composite material, and it is found that the electrode material has excellent conductivity and rate performance.
[0054] Table 1
[0055]
[0056] In summary, the lithium-sulfur battery positive electrode material according to the embodiment of the present application has at least one of the following advantages:
[0057] (1) Two-dimensional layered MXenes exhibit high catalytic activity in electrochemical reactions.
[0058] (2)MXene exhibits excellent adsorption of polysulfides during the charging and discharging process.
[0059] (3) The hollow structure has a higher specific surface area and space, which can alleviate the volume expansion effect.
[0060] (4) The porous hollow 45@HZnSe-CoSe / M / S dodecahedron exhibits high electrochemical performance.
[0061] (5) The porous hollow 45@HZnSe-CoSe / M / S dodecahedron can alleviate the shuttle effect.
[0062] (6) The 45@HZnSe-CoSe dodecahedral cathode material with MXene coated on the surface has good conductivity.
[0063] (7) Electrostatic self-assembly technology has a simple process, strong controllability and good repeatability, and therefore has broad application prospects.
[0064] (8) When the electrodes prepared by the present invention are assembled into a battery, a larger discharge specific capacity and cycle stability can be obtained.
[0065] Although the present disclosure has been described in detail with reference to the specific embodiments of the present application, it will be understood by those skilled in the art that various changes and modifications may be made therein without departing from the spirit and scope of the embodiments. Therefore, the present application is intended to cover the modifications and variations of the present application, and any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included within the scope of the claims of the present application and their equivalents.
[0066] In addition, the features disclosed in the above description or claims or drawings, in their specific form or according to the mode for performing the disclosed functions or the method or process for obtaining the disclosed results, can be used to implement the present application in their different forms alone or in any combination of these features, as appropriate. Specifically, one or more features of any embodiment described in the present application can be combined with one or more features of any other embodiment described in the present application.
[0067] Protection may also be sought for any features disclosed in any one or more of the publications cited in conjunction with the present application and / or incorporated by reference.
Claims
1. A lithium-sulfur battery positive electrode material, characterized in that: The lithium-sulfur battery positive electrode material comprises a two-dimensional MXene nanosheet wrapped with a bimetallic selenide (45@HZnSe-CoSe / M) dodecahedral structure, wherein the lithium-sulfur battery positive electrode material is a hollow structure and is obtained by a 45-minute acid etching technique.
2. The lithium-sulfur battery positive electrode material according to claim 1, characterized in that The HZnSe-CoSe dodecahedron is a porous hollow rhombic dodecahedron, and the average diameter of the porous hollow rhombic dodecahedron particles is 580 nm.
3. A method for preparing a positive electrode material for a lithium-sulfur battery, characterized in that: include: Prepare ZIF-8@ZIF-67 dodecahedron, prepare 45@HZIF based on ZIF-8@ZIF-67 dodecahedron, and prepare HZnSe-CoSe porous hollow dodecahedron based on 45@HZIF; wherein preparing 45@HZIF based on ZIF-8@ZIF-67 dodecahedron comprises: slowly adding tannic acid aqueous solution to ZIF-8@ZIF-67 dispersion and aging for 45 minutes to obtain 45@HZIF dodecahedron; Preparation of MXene colloids; The 45@HZnSe-CoSe porous hollow dodecahedron was mixed with MXene colloid to obtain two-dimensional MXene nanosheets encapsulating 45@HZnSe-CoSe dodecahedron (45@HZnSe-CoSe / M); 45@HZnSe-CoSe / M was subjected to infiltration treatment to obtain 45@HZnSe-CoSe / M / S composite material.
4. The method according to claim 3, characterized in that The steps of preparing ZIF-8@ZIF-67 dodecahedron include: Cobalt nitrate hexahydrate (Zn(NO3)2·6H2O) and 2-methylimidazole (MeIm) were dissolved in methanol respectively, and the two solutions were mixed, and ZIF-8 was obtained through the white precipitate in the mixed solution; Ultrasonic dispersion of ZIF-8 in methanol was performed to obtain a ZIF-8 dispersion; Co(NO3)2·6H2O and MeIm were dissolved in methanol respectively, and the two solutions were added to the ZIF-8 dispersion respectively, and the ZIF-8@ZIF-67 dodecahedron was obtained by precipitating from the mixed solution.
5. The method according to claim 3 or 4, characterized in that: The step of preparing 45@HZIF based on ZIF-8@ZIF-67 dodecahedron further includes: obtaining a ZIF-8@ZIF-67 dispersion based on ZIF-8@ZIF-67; The step of preparing HZnSe-CoSe porous hollow dodecahedron according to 45@HZIF includes: performing selenization reaction on 45@HZIF to obtain 45@HZnSe-CoSe porous hollow dodecahedron.
6. The method according to claim 3, characterized in that The steps of preparing MXene colloid include: The Ti3AlC2-MAX phase ceramic, LiF and HCl are mixed to obtain a mixed solution; The mixed solution is stirred to allow HF generated in the mixed solution to etch Al in the MAX; The mixed solution was washed and centrifuged with deionized water; Deionized water was added to the precipitate of the mixed solution for ultrasonic treatment, and the MXene colloid on the upper layer of the solution after ultrasonic treatment was collected.
7. A lithium-sulfur battery positive electrode sheet, characterized in that: include: A current collector and a coating layer coated on the surface of the current collector, wherein the coating layer comprises a 45@HZnSe-CoSe / M / S composite material prepared according to the preparation method according to any one of claims 3 to 6.
8. The lithium-sulfur battery positive electrode sheet according to claim 7, characterized in that: The coating layer further comprises carbon black and a binder.
9. The lithium-sulfur battery positive electrode sheet according to claim 8, characterized in that: The mass ratio of the 45@HZnSe-CoSe / M / S composite material, the carbon black and the binder is 7:2:
1.
10. The lithium-sulfur battery positive electrode sheet according to claim 8, characterized in that: The mass ratio of the 45@HZnSe-CoSe / M / S composite material, the carbon black and the binder is 6:3:1.
Citation Information
Patent Citations
Preparation method of cobalt-iron bimetal selenide sodium ion battery negative electrode material
CN110943216A
(Zn, Mn)Se / C composite material and preparation method thereof
CN111640944A
Preparation method of heterojunction ZnSe / CoSe2 general carrier based on lithium-sulfur total battery positive and negative electrode protection
CN113571708A
KR20210048052A
